MATHEMATICAL MODEL OF METAL CORROSION RATE WITH ENVIRONMENTAL FACTORS THAT SPEED UP CORROSION - Maghfiroh, Rofila El; Dewi, Mutia Lina; Khusniah, Rif'atul (Universitas Islam Negeri Imam Bonjol Padang, 2024)
Corrosion process often occurs in different types of metals, due to the natural properties of metals. Environmental factors also affect the metals corrosion process, so a mathematical model of metal corrosion rate has been formed with environmental factors accelerating the corrosion process. The mathematical model influenced by initial metal molarity (L), transition metal molarity (N), corrosion product molarity (K), and environmental molarity (X). The mathematical model is a system of diffrential equations whose equilibrium point is then determined. The equilibrium point of the mathematical model of metal corrosion rate with environmental factors that accelerate the corrosion process is stable. Environmental factors that accelerate the corrosion process influence the corrosion product molarity. Corrosion products molarity will reach steady state more quickly if the metal is in an environment that accelerates the corrosion process